(untitled) (Bangladesh Journal of Medical Science, 2025)
Lung cancer remains the leading cause of cancer mortality globally, with non-small-cell lung cancer (NSCLC) accounting for approximately 85% of cases. Focal adhesion kinase (FAK), a non-receptor tyrosine kinase encoded by Protein Tyrosine Kinase 2 (PTK2), integrates signals from integrins and growthfactor receptors to drive cell proliferation, survival, migration, and invasion. Aberrant FAK activation, resulting from gene amplification, overexpression, or crosstalk with receptor tyrosine kinases, contributes to tumor progression and therapeutic resistance. This review synthesizes mechanistic insights into FAK signaling and critically appraises the development of ATPcompetitive FAK inhibitors, including defactinib (VS-6063), GSK2256098 (a novel oral FAK), and VS-4718. We examine their pharmacodynamic effects, safety profiles, and preliminary efficacy when combined with epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors and immune checkpoint blockade. Key challenges and opportunities for clinical translation are addressed, including biomarker development for patient selection, optimization of combination regimens to overcome adaptive resistance, and strategies to integrate FAK-targeted therapies within existing treatment paradigms. By aligning molecular and clinical perspectives with global healthcare realities, this review aims to inform research priorities and facilitate the integration of FAK-targeted therapies into the management of NSCLC worldwide—a graphical abstract illustrated in Figure 1. BJMS, Vol. 24 No. 04 October’25 Page : 1029-1049